Preventive effects of Ophiocordyceps sinensis mycelium on the liver fibrosis induced by thioacetamide. Issue 6 (9th February 2017) - Wu, Yi‐Hsieng Samuel; Tseng, Jung‐Kai; Chou, Chung‐Hsi; Chiu, Chih‐Hsien; Lin, Yi‐Ling; Chen, Yi‐Chen
Abstract: Thioacetamide (TAA), usually used as a fungicide to control the decay of citrus products, itself is not toxic to the liver, but its intermediates are able to increase oxidative stress in livers and further cause fibrosis. Ophiocordyceps sinensis mycelium (OSM) which contains 10% polysaccharides and 0.25% adenosine decreased ( P < 0.05) the lipid accumulation and increased ( P < 0.05) antioxidative capacity in livers of thioacetamide (TAA) injected rats. Meanwhile, the increased ( P < 0.05) liver sizes, serum alanine transaminase (AST) and aspartate transaminase (ALT) values in thioacetamide (TAA)‐injected rats were ameliorated ( P < 0.05) by OSM supplementation. Moreover, the levels of proinflammatory cytokines, such as the tumor necrosis factor‐α (TNF‐α) and interleukin‐1β (IL‐1β), were also reduced ( P < 0.05). The fibrosis phenomena in pathological (Masson's trichrome and H&E stainings) and immunohistochemical [α‐smooth actin (αSMA) and CD86/ED1] observations in TAA‐treated rats were reduced ( P < 0.05) by OSM cotreatment. The protective effect of OSM against TAA‐induced liver inflammation/fibrosis may be via downregulations ( P < 0.05) of TGF‐β pathways and NFκB which further influenced ( P < 0.05) the expressions of fibrotic and inflammatory genes (i. e., αSMA, Col1α, COX2). Therefore, OSM shows preventive effects on the development of TAA‐induced hepatic fibrosis.